Morphine is an arteriolar vasodilator in man - Afshari, Reza; Maxwell, Simon R. J.; Webb, David J.; Bateman, D. Nicholas (British journal of clinical pharmacology, 2009)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • It has been recognized for about 10 years that morphine is a veno‐dilator in man and that this effect may be related to histamine release. WHAT THIS PAPER ADDS • This effect also occurs in the arteriolar system, with vasodilatation at doses of morphine that may have clinical relevance in patients with heart failure, or who abuse opioids. • The effect is mediated by histamine release and actions of nitric oxide. • The mechanisms of this effect of morphine are unclear, but suggest an alternative therapeutic target in vascular disease. AIM The mechanisms of action of morphine on the arterial system are not well understood. The aim was to report forearm vascular responses, and their mediation, to intra‐arterial morphine in healthy subjects. METHODS Three separate protocols were performed: (i) dose ranging; (ii) acute tolerance; (iii) randomized crossover mechanistic study on forearm blood flow (FBF) responses to intrabrachial infusion of morphine using venous occlusion plethysmography. Morphine was infused either alone (study 1 and 2), or with an antagonist: naloxone, combined histamine‐1 and histamine‐2 receptor blockade or during a nitric oxide clamp. RESULTS Morphine caused an increase in FBF at doses of 30 µg min−1[3.25 (0.26) ml min−1 100 ml−1][mean (SEM)] doubling at 100 µg min−1 to 5.23 (0.53) ml min−1 100 ml−1. Acute tolerance was not seen to 50 µg min−1 morphine, with increased FBF [3.96 (0.35) ml min−1 100 ml−1] (P = 0.003), throughout the 30‐min infusion period. Vasodilatation was abolished by pretreatment with antihistamines (P = 0.008) and the nitric oxide clamp (P < 0.001), but not affected by naloxone. The maximum FBF with pretreatment with combined H1/H2 blockade was 3.06 (0.48) and 2.90 (0.17) ml min−1 100 ml−1 after 30 min, whereas with morphine alone it reached 4.3 (0.89) ml min−1 100 ml−1. CONCLUSIONS Intra‐arterial infusion of morphine into the forearm circulation causes vasodilatation through local histamine‐modulated nitric oxide release. Opioid receptor mechanisms need further exploration.